An ergonomics intervention study into the physiological, perceptual and productivity effects of three citrus harvesting bag designs in the Eastern Cape of South Africa : a combined laboratory and field approach - Bassey-Duke, Elizabeth Misan (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2015)
Background: Agriculture plays a vital role in the economy of any industrially developing country, including South Africa. In the Eastern Cape of South Africa citrus farming is a significant contributor to the local economy (Johnson et al., 2005). The harvesting phase of citrus farming is performed manually and exposes workers to physical risks, which can lead to the development of musculoskeletal disorders. In particular, the standard harvesting bag comprises of a single shoulder strap and promotes asymmetrical load carriage which results in shoulder and lower back pain complaints. The current study compared the physiological (EMG), perceptual (RPE), usability (PUEU) and productivity effects of two new harvesting bag designs (a hip belt and a backpack bag design) to the standard harvesting bag design. This was performed in a laboratory as well as a field setting. Methods (Laboratory phase): 36 participants (12 males and 24 females) were assigned to one worker group. The "tall ladder worker" group was comprised of only males and the "step ladder worker" and "ground worker" group of females. Each participant was required to simulate a citrus harvesting task while utilizing each of the bag designs on different days. On each day/test session, participants performed three harvesting cycles. Muscle activity was measured throughout the entire testing session and RPE were recorded at the end of each cycle. Results (Laboratory phase): The EMG and RPE results indicate that the backpack design was the most ideal design to reduce asymmetry, while the standard harvesting bag design was the worst. Although not significant, there was greater muscle asymmetry (p=0.109) and a significantly higher perceived exertion when using the standard bag (p=0.0004), in comparison to using the backpack. Methods (Field phase): 17 Xhosa-speaking citrus harvesters (6 females and 11 males) participated in this study. Each harvester worked with one of the three bag designs on a different day. Productivity of each worker was assessed every hour by recording the number of bags filled with fruit and at the end of the shift. A Perceived Usefulness & Ease of Use questionnaire was presented to each participant to obtain feedback on worker acceptance to the new bag designs. Results (Field phase): A general trend in support of the hip belt bag design over the other two bag designs were found, even within the different worker demographic groups (age, sex and worker experience). The workers perceived less exertion (7.98 ± 1.86) and were more productive (9.90 ± 2.11 bags/hour) when using the hip belt design; they also found this bag the most useful (1.02 ± 0.09) and easy to use (1.07 ± 0.25). In contrast, the backpack bag design had significantly poorer responses when compared to the other two bag designs and this was evident in all the dependent variables assessed (RPE, productivity and PUEU). Conclusion: The results from the laboratory phase supported the expectation that the backpack bag design reduces asymmetry and hence, is more suitable than the standard harvesting bag. However, results from the field show that the hip belt bag design was the most preferred and the backpack was the least preferred. Bao & Shahnavaz (1989) highlight the need for ergonomics researcher to convey laboratory findings into the field context. However, as shown by the current study, there are numerous challenges associated with field work, making it difficult for laboratory findings to be successfully conveyed to the field. Limitations and Recommendations: For the laboratory phase of the project, no biomechanical and cardiovascular responses were assessed. However, for a holistic approach, these variables should be considered in future studies. Due to high variability from one harvesting cycle to another, more than three harvesting cycles should also be performed to accurately replicate the harvesting process as done in the field over extended durations of time. For the field phase, data should be collected from more than one citrus farm and thus a larger sample size could be obtained. This would improve the validity of the study. In addition to this, data should be collected for a full working day, especially if environmental conditions are not a hindrance, as well as for a whole season, since workloads vary, depending on the time of the harvesting season.,Name on Graduation Programme: Bassey-Duke, Elizabeth Missan
Keywords: Citrus -- Harvesting -- South Africa -- Eastern Cape; Lifting and carrying -- South Africa -- Eastern Cape; Manual work -- South Africa -- Eastern Cape; Blue collar workers -- South Africa -- Eastern Cape; Work -- Physiological aspects; Human mechanics